Conformational and structural diversity of iridium dimethyl sulfoxide complexes. Issue 6 (27th October 2017) - Ridgway, Benjamin M.; Foi, Ana; Corrêa, Rodrigo S.; Bikiel, Damian E.; Ellena, Javier; Doctorovich, Fabio; Di Salvo, Florencia
Abstract : Iridium(III) dimethyl sulfoxide complexes, analogues to clinically significant metallodrugs, exhibiting different rotamers in their solid‐state structures are investigated. The effect of the amount of the crystallized water and the hydrogen‐bonded network in their supramolecular structures on the conformational preferences is studied. Abstract : Transition metal complexes containing dimethyl sulfoxide (DMSO) are important precursors in catalysis and metallodrugs. Understanding the solid‐state supramolecular structure is crucial for predicting the properties and biological activity of the material. Several crystalline phases of DMSO‐coordinated iridium anions with different cations, potassium (1 a ) and n ‐butylammonium (1 b ), were obtained and their structures determined by X‐ray crystallography. Compound (1 a ) is present in two solvatomorphic forms: α and β; the β form contains disordered solvent water. In addition, the structures exhibit different rotamers of the trans ‐[IrCl4 (DMSO)2 ] − anion with the trans ‐DMSO ligands being oriented in anti and gauche conformations. In consideration of these various conformers, the effects of the crystallized solvent and intermolecular interactions on the conformational preferences of the anion are discussed. In addition, density functional theory calculations were used to investigate the energies of the anions in the different conformations. It was found that hydrogen bonds between water and the DMSO complex stabilize the gauche conformation which is the least stable form of the trans ‐DMSO complex. Consequently, by controlling the number of hydrogen‐bond donors and acceptors and the amount of water, it may be possible to obtain different solvatomorphs of clinically significant metallodrugs.